2022
DOI: 10.1093/biolre/ioac220
|View full text |Cite
|
Sign up to set email alerts
|

Decreased B7-H3 promotes unexplained recurrent miscarriage via RhoA/ROCK2 signaling pathway and regulates the secretion of decidual NK cells

Abstract: The cause for at least 50% of recurrent miscarriages (RM) is unclear, defined as unexplained recurrent miscarriages (uRM). B7-H1 (PD-L1), a molecule of the B7 family, promotes tumor development by modulating immune evasion, and recent researchers have also attached importance to the role of B7-H3, another molecule of B7 family, in tumor. Based on the similarity between growth and immune response in tumors and pregnancy, we first explored the role of B7-H3 in uRM. We found reduced levels of B7-H3 in villus tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…113 Elevated levels of BDNF enhance the ability of cells to migrate and invade by regulating the activation of RhoA, 115 a protein that regulates signaling pathways associated with cytoskeletal remodeling during cell migration. 11,116 It was found that the change in the expression and activation of various Rho isoforms under the influence of other growth factors, in particular IGF1, EGF and TGFβ, plays a role in the organization of the actin skeleton of trophoblast cells and modulates the migration of HTR-8/SVneo, Jeg-3, and JAR cells. [117][118][119][120] However, the possibility of activation of Rho-dependent migration of trophoblast cells during the induction of NTs has not yet been studied.…”
Section: Neurotrophins and Pregnancymentioning
confidence: 99%
See 2 more Smart Citations
“…113 Elevated levels of BDNF enhance the ability of cells to migrate and invade by regulating the activation of RhoA, 115 a protein that regulates signaling pathways associated with cytoskeletal remodeling during cell migration. 11,116 It was found that the change in the expression and activation of various Rho isoforms under the influence of other growth factors, in particular IGF1, EGF and TGFβ, plays a role in the organization of the actin skeleton of trophoblast cells and modulates the migration of HTR-8/SVneo, Jeg-3, and JAR cells. [117][118][119][120] However, the possibility of activation of Rho-dependent migration of trophoblast cells during the induction of NTs has not yet been studied.…”
Section: Neurotrophins and Pregnancymentioning
confidence: 99%
“…Despite the fact that several hypotheses have been proposed for the development of immune tolerance during normal pregnancy, 1–5 there is still no understanding of the exact mechanisms. Therefore, research aimed at studying the relationship between invasive trophoblast cells and maternal NK cells, in particular decidual NK (dNK) cells, is of particular interest 6–11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reasons for this imbalance can be manifold, including systemic immune alterations, genetic constitution, inflammatory effectors including immune disorders, stress, diet, physical exercises, and obesity, or altered activators including paternal factors, HLA matching, genetics of the embryo, and more. On a cellular basis, not only local immune cells but also trophoblast cells, as well as decidual epithelial and stromal cells, affect the balance by activating and inhibiting soluble and cell-to-cell-contact-mediated factors and receptors [ 24 , 42 , 51 , 52 , 97 , 98 , 99 , 100 ].…”
Section: Immune Implications In Adverse Pregnancy Outcomesmentioning
confidence: 99%
“…Similarly, to immune cells in the decidua, angiogenetic and invasive processes can be supported by immune cells in the tumor microenvironment. Both tumor and trophoblastic cells express immune inhibitory ligands, including B7 family molecules such as programmed cell death ligand (PD-L) 1, PD-L2, CD80, and CD86 [ 23 , 24 ], and T cell immunoglobulin and mucin-domain containing-3 ligand (TIM-3L) [ 25 ]. Similar to the immune cells, such as macrophages and NK cells, which support trophoblast invasion, the presence of tumor-associated macrophages (TAMs) is associated with tumor progression and metastasis [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%